Cyber Notaris dalam Penyimpanan Minuta Akta: Studi Legalitas dalam Bukti Kekuatan di Persidangan - Jamilah (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
This research is motivated by the development of notary services in the digital era, the use of information technology is increasingly widespread, including in the legal field. Many countries have adopted the practice of storing documents in digital form, including minutes of deeds made by a notary. The legal system has an important role in ensuring justice and legal certainty for society. In the legal system, the strength of evidence is a very important element in building arguments and making the right decisions in court. The research methods used in this research include analysis of notary documents covering policies and regulations, surveys of several notary institutions, interviews with several contributing informants, and analysis of trial results. Following the results of research conducted that the legality and strength of evidence from the use of Cyber Notaries in storing minutes of the deed. Cyber Notary refers to a notary who uses digital technology and electronic platforms to carry out notarial tasks including keeping the minutes of the deed. The use of a Cyber Notary in keeping minuta deeds has legally recognized legality. In many jurisdictions, regulations, and policies have been introduced to regulate the use of technology in notary practice. This shows an acknowledgment of the validity of the documents kept by the Cyber Notary.